All methacrylate block copolymer/TiO2 nanocomposite via ATRP and in-situ sol-gel process. (March 2020) - Gnanaseelan, Minoj; Kalita, Uddhab; Janke, Andreas; Pionteck, Jürgen; Voit, Brigitte; Singha, Nikhil K.
Graphical abstract: Abstract: This investigation reports the preparation and characterisation of all methacrylate block copolymer (BCP)/TiO2 nanocomposites via atom transfer radical polymerisation (ATRP). For that, a poly(methyl methacrylate)- block -poly(2-hydroxyethyl methacrylate) (PMMA- b -PHEMA) with relatively narrow molecular weight distribution was prepared by ATRP. The phase-separated morphology of the BCP was proven by AFM analysis. Finally, the BCP/TiO2 nanocomposites were prepared by an in-situ sol-gel process in presence of the BCP. The generated TiO2 nanoparticles are finely and homogeneously dispersed within the BCP because of the specific interaction of TiO2 with the PHEMA block. The presence of nanoparticles shifts the glass transition of the BCP to higher temperature and affects the thermal degradation generating rather high ash contents. High refractive index of 1.64 in combination with high transparency was achieved for polymer films at a relatively low loading of 15 wt.% TiO2 making the nanocomposites suitable for potential optical application.